Da Whatsapp al Flaming il passo è breve. Usi ed effetti degli Smartphones dei nativi digitali tra web reputation e devianza on line - Riccardo Giumelli (Culture e Studi del Sociale)
The text starts from a research carried out in the Verona schools where we wanted to inves-tigate the uses and effects of Smartphones and social networks. The results also report the forms of cyberbullying exercised among the students. We will discuss this by focusing on the forms of hate speech and flaming. Before delving in to the analysis of the collected da-ta, we have reflected on the dialectic never ceased if the means of communication or its us-ers create the perverse and deviant effects that emerge. Rather than taking a position, in one way or another, a complexity of the issue emerges where the worst option is to take radically one of these opposing positions. We cannot deny how social networks have favored an extension and diffusion of flaming, as the students themselves tell. But, at the same time, it is naive to believe that there are no responsibilities of the users. In the background, there is a theme that prevails, that of a new hyperconnected generation, the always-connected generation, everywhere and the research try to understand better this generation in order to prepare us with the challenges that already are in front of us.